Dari Privasi ke Eksploitasi : Memetakan Jejak Kriminalisasi Revenge Porn dalam Era Media Sosial - Zul Khaidir Kadir (Dewantara : Jurnal Pendidikan Sosial Humaniora, 2025)
Revenge porn is a form of technology-based sexual violence that is increasingly developing in the digital era. This crime not only violates privacy, but also involves sexual exploitation through the distribution or threat of distribution of intimate content without consent. Unfortunately, the impact of this crime on female victims is enormous, and the legal systems in many countries still show weaknesses in dealing with its complexity. This study explores revenge porn from a criminological perspective, focusing on the perpetrator's action patterns, the vulnerability of victims, and the weaknesses of existing regulations. This study uses a normative legal research method with a conceptual approach. The data collection method was collected using a literature study and then analyzed using qualitative methods and presented descriptively. The results of the study show that revenge porn has a multidimensional impact on victims and the general public. In addition, weaknesses in regulations are still an obstacle in providing protection for victims. Existing regulations are limited to violations of privacy without considering the dimensions of sexual exploitation, gender dynamics, or the psychological impacts experienced by victims. Therefore, legal reform is needed that includes a clear definition, recognition of the gender dimension, and closer international cooperation.